Infection and transmission of Cache Valley virus by Aedes albopictus and Aedes aegypti mosquitoes - Victoria B. Ayers (Parasites & Vectors, 2019)
Abstract Background Cache Valley virus (CVV; Bunyavirales, Peribunyaviridae) is a mosquito-borne arbovirus endemic in North America. Although severe diseases are mainly observed in pregnant ruminants, CVV has also been recognized as a zoonotic pathogen that can cause fatal encephalitis in humans. Human exposures to CVV and its related subtypes occur frequently under different ecological conditions in the New World; however, neurotropic disease is rarely reported. High prevalence rates of neutralizing antibodies have been detected among residents in several Latin American cities. However, zoophilic mosquito species involved in the enzootic transmission are unlikely to be responsible for the transmission leading to human exposures to CVV. Mechanisms that lead to frequent human exposures to CVV remain largely unknown. In this study, competence of two anthropophilic mosquitoes, Aedes albopictus and Ae. aegypti, for CVV was determined using per os infection to determine if these species could play a role in the transmission of CVV in the domestic and peridomestic settings of urban and suburban areas. Results Aedes albopictus were highly susceptible to CVV whereas infection of Ae. aegypti occurred at a significantly lower frequency. Whilst the dissemination rates of CVV were comparable in the two species, the relatively long period to attain maximal infectious titer in Ae. aegypti demonstrated a significant difference in the replication kinetics of CVV in these species. Detection of viral RNA in saliva suggests that both Ae. albopictus and Ae. aegypti are competent vectors for CVV under laboratory conditions. Conclusions Differential susceptibility to CVV was observed in Ae. albopictus and Ae. aegypti, reflecting their relatively different capacities for vectoring CVV in nature. The high susceptibility of Ae. albopictus to CVV observed in this study suggests its potential role as an efficient vector for CVV. Complemented by the reports of multiple CVV isolates derived from Ae. albopictus, our finding provides the basis for how the dispersal of Ae. albopictus across the New World may have a significant impact on the transmission and ecology of CVV.